Medium- to long-term clinical and functional outcomes of isolated and combined subscapularis tears repaired arthroscopically - Augusto Cigolotti; Carlo Biz; Erik Lerjefors; Gianfranco de Iudicibus; Elisa Belluzzi; Pietro Ruggieri (Archives of Medical Science, 2020)
Introduction The purpose of this study was twofold. First, the efficacy of arthroscopic repair in patients with full thickness, isolated subscapularis tendon tears (I-STTs) or combined subscapularis tendon tears (C-STTs) involving the rotator cuff tendons was evaluated. Second, the outcomes between these two groups were compared. The influence of age and gender on the cohort clinical outcomes was also analysed. Our hypothesis was that satisfactory functional results could be obtained arthroscopically in both groups without any influence of age or gender.